Analysis of Presentation of Income Account Financial Statements at The Madeline Hotel Bengkulu - Susi Yanti; Ida Anggriani; Rinto Noviantoro (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The presentation of financial statements of income accounts at The Madeline Hotel Bengkulu aims to find out how to apply the peresentation of financial statements to existing income accounts at The Madeline Hotel Bengkulu.The data analysis technique used in this research is descriptive qualitative analysis, which to compare the existing theory with actual practice so that conclusioncan ce drawn. The steps taken are to explain the financial statements of income accounts at The Madeline Hotel Bengkulu within a certain period and compare the statements of accounting standards to revenue recognition at The Madeline Hotel Bengkulu.The results of the study concluded that the presentation of the income account financial statements of The Madeline Hotel Bengkulu was in accordance with the revenue recognition in the Statement of Financial Accounting Standards (PSAK) No. 23 By doing q good analysis of cost and income calculation.